1979
DOI: 10.1128/jb.140.1.14-19.1979
|View full text |Cite
|
Sign up to set email alerts
|

Mutant single-strand binding protein of Escherichia coli: genetic and physiological characterization

Abstract: The mutant (ssb-1) is also more sensitive to ultraviolet irradiation and about onefifth as active in recombination. Single-strand binding protein is thus implicated in repair and recombination as well as in replication. The mutation in ssb is located between uvxrA and melA at 90.8 min on the genetic map. The ssb gene appears to be allelic with lexC, a gene with a proposed role in regulating inducible deoxyribonucleic acid repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…The interaction of many proteins with the SSB C-terminal tail is disrupted by mutation of the penultimate amino acid Pro 176 to Ser (33). Strains carrying this mutation (ssb-113, originally lexC113) are temperature sensitive and quite compromised (34,35). To investigate this question, we constructed W3110 topB-ecgfp S mCherry-dnaN ssb-113 (CL281) and compared Topo III and ␤ localization with that in the wild-type strain (CL109) at 30°C in minimal medium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of many proteins with the SSB C-terminal tail is disrupted by mutation of the penultimate amino acid Pro 176 to Ser (33). Strains carrying this mutation (ssb-113, originally lexC113) are temperature sensitive and quite compromised (34,35). To investigate this question, we constructed W3110 topB-ecgfp S mCherry-dnaN ssb-113 (CL281) and compared Topo III and ␤ localization with that in the wild-type strain (CL109) at 30°C in minimal medium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature defect of SSB‐113 in in vitro reactions using Pol III holoenzyme is explained further in the Discussion. Alternatively, the χ–SSB contact is involved in the repair‐ and recombination‐defective phenotypes of SSB‐113 that occur at all temperatures examined (Glassberg et al ., 1979; Vales et al ., 1980; Golub and Low, 1983; Lieberman and Witkin, 1983; Whittier and Chase, 1983; Laine and Meyer, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo studies have shown that, in addition to their well known roles in DNA replication, E.coli SSB protein (Glassberg et al, 1979), T4 gene 32 protein (Tomizawa et al, 1966;Berger et al, 1969;Mosig et al, 1979) and T7 gene 2.5 protein (Araki and Ogawa, 1981) are also involved in recombination. However, the multiple reactions in which these proteins participate have made it difficult to dissect their contributions to recombination and replication since they may serve identical roles in both processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, other proteins can mediate some of the subsequent steps in recombination equally as well as the RecA-type protein. For example, the single-stranded DNA (ssDNA) binding proteins, of which the E.coli SSB protein and the T4 gene 32 protein are examples, stimulate the annealing of complementary DNA strands (Chase and Williams, 1986), and in vivo studies have shown that both are involved in recombination (Tomizawa et al, 1966;Berger et al, 1969;Glassberg et al, 1979;Mosig et al, 1979). Under some conditions these proteins stimulate strand exchange mediated by the RecA (McEntee et al, 1980;Radding, 1982) and UvsX (Formosa and Alberts, 1986;Kodadek, 1990) proteins, but they can also inhibit strand transfer (Kodadek, 1990).…”
Section: Introductionmentioning
confidence: 99%